2013
DOI: 10.1371/journal.pone.0055275
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Vitamin D in Systemic Lupus Erythematosus: A Systematic Review

Abstract: BackgroundVitamin D deficiency is more prevalent among SLE patients than the general population. Over the past decade, many studies across the globe have been carried out to investigate the role of vitamin D in SLE from various clinical angles. Therefore, the aim of this systematic review is to summarise and evaluate the evidence from the published literature; focusing on the clinical significance of vitamin D in SLE.MethodsThe following databases were searched: MEDLINE, Scopus, Web of Knowledge and CINAHL, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 30 publications
4
36
0
3
Order By: Relevance
“…One possible explanation for the association between SLE and vitamin D deficiency is the universal recommendation that these patients should avoid sunlight exposure [7]. Moreover, many drugs used in SLE management, such as glucocorticoids and hydroxychloroquine, may interfere with vitamin D metabolism and 25-hidroxyvitamin D (25(OH)D) serum levels [8]. It has also been suggested that vitamin D deficiency might be a risk factor for the development of the disease, although vitamin D intake was not associated with the risk of SLE development in a prospective study [9].…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the association between SLE and vitamin D deficiency is the universal recommendation that these patients should avoid sunlight exposure [7]. Moreover, many drugs used in SLE management, such as glucocorticoids and hydroxychloroquine, may interfere with vitamin D metabolism and 25-hidroxyvitamin D (25(OH)D) serum levels [8]. It has also been suggested that vitamin D deficiency might be a risk factor for the development of the disease, although vitamin D intake was not associated with the risk of SLE development in a prospective study [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is worth considering subsidisation of oral vitamin D (vitamin D 3 , 1000 IU as a maintenance daily dose) in this high risk population group. Such a strategy will invariably improve the drug compliance, potentially reduce the non‐fatal and fatal cardiovascular outcomes also have the potential to deliver other skeletal and non‐skeletal benefits …”
Section: Discussionmentioning
confidence: 99%
“…Such a strategy will invariably improve the drug compliance, potentially reduce the non-fatal and fatal cardiovascular outcomes also have the potential to deliver other skeletal 18,19 and non-skeletal benefits. [20][21][22] Individuals with moderate or severe VDD are recommended to take higher doses (3000-5000 IU/day) of vitamin D under medical supervision for 6-12 weeks until the repletion of body stores and then can follow the daily maintenance dose. 14 There is some suggestion that with universal vitamin D supplementation the frequency of vitamin D testing could be eased, and thereby the mounting costs associated with vitamin D testing could be curtailed.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of vitamin D are also present in the healthy population; therefore, it is difficult to evaluate the clinical significance of the high prevalence of vitamin D deficiency in patients with autoimmune diseases, which has been confirmed by several cross-sectional studies. Very low levels of vitamin D (< 10 ng/mL) are associated with certain symptoms and correlate with disease activity in SLE [99][100][101]. Several factors can influence the level of vitamin D in patients with scleroderma, as skin fibrosis can be altered with sun exposure and gut involvement can lead to malabsorption.…”
Section: Skin Involvement and Digital Vasculopthymentioning
confidence: 99%